2019
DOI: 10.12968/jowc.2019.28.11.730
|View full text |Cite
|
Sign up to set email alerts
|

Biomodulation induced by fluorescent light energy versus standard of care in venous leg ulcers: a retrospective study

Abstract: Objective: The recently completed EUREKA study confirmed the efficacy and safety profile of fluorescent light energy (FLE) in treating hard-to-heal wounds. To supplement the EUREKA prospective, observational, uncontrolled trial results, researchers selected one of the EUREKA clinical centres to conduct a retrospective analysis of matching wound care data for 46 venous leg ulcers (VLU) patients who had received standard wound care over a five-year period, compared with 10 EUREKA VLU subjects. Method: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Also, the mean relative wound area regression (RWAR) was 32% (6 weeks) and 50% (16 weeks) as compared to the matching group (wound age, size, patient's age, and gender), which is −3% and −6% for 6 and 16 weeks, respectively. [137] NATROX oxygen wound therapy is a class II, novel, one-timeuse medical device. It constitutes i) a portable, reusable oxygen generator with a rechargeable battery and ii) a proprietary wheelshaped oxygen delivery system (ODS).…”
Section: Wound Care Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the mean relative wound area regression (RWAR) was 32% (6 weeks) and 50% (16 weeks) as compared to the matching group (wound age, size, patient's age, and gender), which is −3% and −6% for 6 and 16 weeks, respectively. [137] NATROX oxygen wound therapy is a class II, novel, one-timeuse medical device. It constitutes i) a portable, reusable oxygen generator with a rechargeable battery and ii) a proprietary wheelshaped oxygen delivery system (ODS).…”
Section: Wound Care Devicesmentioning
confidence: 99%
“…Also, the mean relative wound area regression (RWAR) was 32% (6 weeks) and 50% (16 weeks) as compared to the matching group (wound age, size, patient's age, and gender), which is −3% and −6% for 6 and 16 weeks, respectively. [ 137 ]…”
Section: Commercial Products For Chronic Wounds Treatmentmentioning
confidence: 99%
“…To generate fluorescence, specialized chromophores (light absorbing molecules) are employed to translate light energy into a low-energy emission of fluorescence through a mechanism known as stokes shift [36]. FLE is a unique form of photobiomodulation that has been demonstrated to advance healing of both acute and chronic wounds [37,38]. Studies have demonstrated that acute incisional wounds have reduced inflammation, as well as more physiologic re-epithelization and collagen remodeling resulting in better quality and less visible scars [25][26][27]39].…”
Section: Introductionmentioning
confidence: 99%